Konsep Syukur Berdasarkan Etos Kerja Dalam Prespektif Hadis : Studi Kasus : KSPPS BMT Al-Iktisab Kebun Baru Jatim - Wasilaturohmah, Wasilaturohmah; Fadllan, Fadllan (Ulumuna: Jurnal Studi Keilsman, 2024)
Work ethic is defined as a guideline that is oriented towards divine (divine) values. Work ethic is related to achieving material prosperity. This is based on the desire to gain reward or the approval of Allah SWT, so that the work ethic that is carried out becomes a religious and worldly value. There are also those who want to receive material rewards in the form of money or salary, in order to meet their family's needs. However, sometimes rewards in the form of material are sometimes misinterpreted as getting as much reward as possible which will then only be used for fun. In this case, Islam emphasizes several concepts such as patience, honesty and trust in what has been received as a result of the efforts made. This research aims to analyze the concept of gratitude based on work ethic from a hadith perspective carried out at KSPPS BMT Al-Iktisab Kebun Baru, East Java. The approach used is a literature review approach and case studies with qualitative research, then the explanation is strengthened from related articles or research. This data was obtained from hadith books and articles. Then, the data is described from various aspects related to the content analysis method. The results of this research are: 1) The concept of gratitude used in this context teaches the general public to be grateful to humans by sincerely accepting what has been given, so this creates gratitude in the form of thanking Allah SWT. 2) The work ethic that each employee carries out in carrying out their work can make them considered good and get positive views from various parties. 3) Based on the perspective of the hadith that has been explained, it strengthens employees at KSPPS BMT Al-Iktisab Kebun Baru Jatim to continue to be enthusiastic in working, be sincere with what they get and foster a sense of responsibility within themselves. 4) The importance of the concept of gratitude based on the work ethic carried out by employees in all fields of work makes the work they do worth worship and fosters a sense of confidence that everything that happens is determined by Allah SWT.